Experiences, perceptions and attitudes on providing advice on physical activity to patients with chronic ischaemic heart disease: a qualitative study in general practitioners in Germany - Norbert Donner-Banzhoff; Rik Crutzen; Sabrina Kastaun; Verena Leve; Stefan Wilm; Alicia Prinz; Sabrina Hoppe (Family Medicine and Community Health)
Background and objective The WHO emphasises the importance of integrating advice on physical activity (PA) into primary care of patients with chronic ischaemic heart disease (IHD). Similarly, the German treatment guideline ‘Chronic Coronary Heart Disease’ recommends that general practitioners (GPs) provide advice on PA to IHD patients. However, the provision of PA advice seems to be inadequately implemented in general practice. One reason is the lack of medical training in providing PA advice effectively and efficiently. International guidelines recommend such training for health professionals. This study aims to explore experiences, perceptions and attitudes, including barriers and facilitators of GPs towards the routine delivery of PA advice to IHD patients.Methods Between March and June 2023, 12 face-to-face problem-centred interviews and six focus group discussions (n=37) with GPs were conducted. Interview and discussion guides were developed and pilot tested by the multi-professional study team. We used a purposive sampling strategy, and data were collected in an iterative process. Audio-recorded data were transcribed verbatim and analysed using a content structuring procedure (deductive and inductive approach). GPs were involved throughout the entire research process, for example, in multi-professional analysis groups.Results Although GPs are mostly aware of the health benefits of PA for patients with IHD, PA advice is not routinely provided. Conversations on PA tend to be rather unstructured, and advice is often addressed more generally than customised to the patients’ needs and preferences. Priority is given to other lifestyle issues, such as smoking cessation. PA advice is perceived as time-consuming and rather ineffective with regard to the target behaviour. GPs frequently express frustration in this context. GPs express a lack of and simultaneously a need for communication strategies (structure and tools) that can be integrated into everyday GP practice to motivate patients to PA.Conclusion The results provide relevant insights into the current practice of GPs with regard to their attitudes on, experiences with, and requirements for the provision of PA advice to IHD patients. These results are helpful to inform the development of appropriate GP training in the provision of very brief PA advice to IHD patients.